Epidemic of venereal treponematosis in wild monkeys: a paradigm for syphilis origin. (May 2020) - Mediannikov, O.; Fenollar, F.; Davoust, B.; Amanzougaghene, N.; Lepidi, H.; Arzouni, J.-P.; Diatta, G.; Sokhna, C.; Delerce, J.; Levasseur, A.; Raoult, D.
Abstract: Treponema   pallidum infections have been primarily known as slightly contagious mucocutaneous infections called yaws (tropical Africa and America) and bejel (subtropical North Africa). T. pallidum emerged as a highly infectious venereal syphilis agent in South America, probably about 500 years ago, and because of its venereal transmission, it quickly caused a worldwide pandemic. The disease manifests as lesions, including a chancre; then antibodies become detectable when or slightly after the chancre appears, and before the development of a rash and other systemic manifestations. Venereal diseases are poorly known in monkeys. During fieldwork in Senegal, we discovered an epizootic outbreak of venereal disease that we explored. We detected a venereal form of T. pallidum subsp. pertenue infection in green monkeys ( Chlorocebus sabaeus ), then observed an epizootic outbreak in Senegal and its spread among baboons a year later. Comparative analysis of T. pallidum genomes from the monkeys' chancres and other Treponema genomes showed an acceleration of the number of single nucleotide polymorphisms, comparable to that observed in syphilis. Identified T. pallidum clones seem to be epizootic through the acceleration of their mutation rate, which is linked to their larger diffusion.